A meta-synthesis on technology-based learning among healthcare students in Southeast Asia - Romli, Muhammad Hibatullah; Wan Yunus, Farahiyah; Cheema, Manraj Singh; Abdul Hamid, Hafizah; Mehat, Muhammad Zulfadli; Md Hashim, Nur Fariesha; Chan, Choong Foong; Wei, Han Hong; Jaafar, Mohamad Hasif (Springer Link, 2022)
Healthcare education providers are eager to apply technologies in teaching and learning activities; however, students are the consumers in higher education, and their opinion and experience should be considered. We performed a meta-synthesis of qualitative studies to help inform our understanding of Southeast Asian healthcare students’ perceptions and experience of technology-based teaching and learning in their education. Our search strategy located 1599 articles from a dozen electronic research databases. Articles were analyzed for quality using the Hawker’s Evidence Appraisal Tool, and 23 qualitative studies were included in the final meta-synthesis. Technologies investigated largely involved online or blended learning, with fewer exploring virtual reality, simulations, telehealth, game-based learning, and videos. Three overarching themes were synthesized: (i) culture does matter in the implementation of technology-based learning; (ii) the values and limitations of technology used for learning; and (iii) technology is part of daily life and creates new challenges in education. Technology is an asset to enhance the learning experience, but educators must be aware of its limitations. Pre-coronavirus disease 2019 (COVID-19) studies were more focused on technology and product, and were optimistically reported, whereas COVID-19–spanning studies focused on life experience and paid more attention to reporting on the inherent challenges. The educational approaches, theories, cultural aspects, and availability of facilities all play a vital role in steering successful technology use in learning.